Run-Time Monitoring Environments for Real-Time and Safety Critical Systems - Nelissen, Geoffrey (2017)
Demo in Demo Session, 22nd IEEE Real-Time Embedded Technology & Applications Symposium (RTAS 2016). 11 to 14, Apr, 2016. Austria.